Bordetella Bronchiseptica in the Immunosuppressed Population – A Case Series and Review. - Abraham Tareq Yacoub; Mitsuya Katayama; JoAnn Tran; Ronit Zadikany; Manasa Kandula; John Norman Greene (Mediterranean Journal of Hematology and Infectious Diseases, 2014)
Organisms that are not known to cause serious infection in the immunocompetent population can in fact cause devastating illness in immunosupressed neutropenic populations especially those who are undergoing hematopoietic stem cell transplantation (HSCT), and solid organ transplantation or a history of malignancy.  One organism of interest isolated from immunosupressed patients at our institution was Bordetella bronchiseptica. B. bronchiseptica is a Gram-negative, rod shaped bacterium, primary respiratory tract organism known to cause respiratory tract disease in the animal population which include dogs, cats, and rabbits. This organism rarely causes serious infection in the immunocompetent population. However; in immunosupressed patients, it can cause serious pulmonary disease. We present three cases of B. bronchiseptica isolated from patients with a history of malignancy a serious pulmonary infection.